Nematode infection on beef cattle in two different productive regions of Argentina's Northwest - Suarez, Victor Humberto; Martinez, Gabriela Marcela; Micheloud, Juan Francisco (2017)
Cattle production in northwest Argentina (NOA) in the last 10 years has grown in importance. However, this growth of livestock brought productive and health constraints such as infection with gastrointestinal nematodes (GIN). Nematode infection may reduce productivity of grazing cattle [1-5]. Free-living forms of GIN exhibit a close relationship with climatic factors, the environment and animal management, affecting GIN development, survival and final infestation rate of pastures [1-7].